(untitled) (Journal of Agriculture & Rural Development, 2010)
The experiment was conducted at the Regional Agricultural Research Station, Ishurdi, Pabna during the growing season 2005-2006 to estimate the genetic diversity among 24 genotypes of pointed gourd by using Mahalanobis D² statistics for nine characters. The genotypes were grouped in to five clusters. The cluster I and III consisted of highest number of genotypes and it was six. The cluster IV contained the lowest number of genotypes and it was three. The clustering pattern of the genotypes under this study revealed that the genotypes collected from the same location were grouped into different clusters. The genotypes of Kushtia were distributed in different clusters. The inter cluster distance were larger than the intra cluster distance suggesting wider genetic diversity among the genotypes of different groups. The highest intra cluster distance was computed for cluster IV (35.80) and the minimum intra cluster distance was found in cluster III (18.37). The clusters IV and II were more diverse as indicated by maximum inter cluster distances between them (41.56) and the minimum inter cluster divergence was observed between cluster III and II (6.84). Cluster II had the highest cluster mean value for number of fruits per plant (391), weight of fruit per plant (11.72kg) and yield (35.28t/ha). Genotypes of the cluster V had late maturity. Key words: Genotype; genetic diversity; pointed gourd. DOI: 10.3329/jard.v7i1.4426 J Agric Rural Dev 7(1&2), 87-92, June 2009